Bridging the evidence-to-action gap: enhancing alignment of national nutrition strategies in Cambodia, Laos, and Vietnam with global and regional recommendations - Nguyen, Tuan Thanh; Huynh, Ngoc Long; Huynh, Phuong Nam; Zambrano, Paul; Withers, Mellissa; Cashin, Jennifer; Chin, Sedtha; Mathisen, Roger (Frontiers in Nutrition, 2024)
Nutrition policies are critical frameworks for tackling the triple burden of malnutrition, including undernutrition (i.e., stunting and wasting), overweight, and hidden hunger (i.e., micronutrient deficiencies). We examined 1) the alignment of recent National Nutrition Strategies and Action Plans (NNS) in Cambodia, Laos, and Vietnam with recent global and regional recommendations and standards with a focus on maternal, infant, and young child nutrition and 2) changes compared to the previous NNS. We extracted information regarding the context, objectives, interventions, indicators, strategies, and coordination mechanisms from the most recent NNSs in Cambodia (2019-2023), Laos (2021-2025), and Vietnam (2021-2030). Recent NNSs aimed to reduce malnutrition among priority populations and described program development, monitoring, and evaluation plans for the following interventions: breastfeeding promotion, improved complementary feeding, dietary diversity, safe water, food security, nutritional/health campaigns, strategies for vulnerable groups, and strengthening of policies related to food and nutrition. Direct interventions to improve women’s general nutrition (outside of pregnancy) and adolescent nutrition were not the focus of any NNSs. Although some indicators (e.g., wasting and exclusive breastfeeding) were covered in all recent NNSs, other indicators (e.g., low birth weight and childhood overweight and obesity) were inconsistently incorporated. In comparison to the previous NNS, the following interventions were discontinued in three countries: dietary counseling, maintaining physical activity, monitoring weight gain during pregnancy, maternal micronutrient supplementation, and nutrition and HIV. Despite similarities in structure and content, the recent NNSs of Cambodia, Laos, and Vietnam do not consistently align with global and regional recommendations. Variations in the types of interventions and indicators included may reflect a shift in priorities, attention, or resources. In conclusion, the NNSs of Cambodia, Laos, and Vietnam exhibit both structural and content similarities; however, certain interventions and indicators vary across countries and differ from global and regional recommendations. Enhancing alignment while prioritizing country-specific needs, optimizing coordination, ensuring policy efficacy, and updating nutrition strategy data for cross-country comparisons and knowledge exchange is critical to ensure progress on reducing malnutrition in the region.